Use of Cable Vibration Isolators for Vibration Protection of Quartz Generators - V. N. Kiyko; N. M. Naumovich; M. V. Davydov; V. I. Zhuravliov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Vibration isolators with damping properties of steel multiwire cables for vibration protection of quartz oscillators have been studied. Modeling of vibration characteristics of structural elements was carried out using numerical methods. The elastic characteristics and design parameters of the cable for the vibration isolator are calculated. A harmonic analysis was carried out with given values of mass and stiffness under the influence of external vibrations. A sample of a cable vibration isolator has been developed and manufactured. To verify the calculated results obtained, the structure of the test bench is proposed, which allows determining the values of na tural re sonant frequencies. The study of the dependence of vibration acceleration on the frequency of oscillations with a disturbing effect according to the sinusoidal and random laws with a variable frequency in the range of 10–2000 Hz was carried out. Tests of the cable vibration isolator have shown the effectiveness of vibration suppression for frequencies above 120 Hz. In the lower range of random vibrations, various resonances have a significant effect on each other. The experiments confirmed the simulation results and the effectiveness of the solution used: the difference in indicators in determining the resonant frequencies was less than 10 % with a decrease in the vibration level to a given indicator.